Pengenalan Mufrodat Bahasa Arab Melalui Permainan Ular Tangga Pada Anak Usia Dini - Maulidya Ulfah; Durtam Durtam; Imas Maesaroh (SELING: Jurnal Program Studi PGRA, 2019)
Language development is very important in early childhood, because it can provide a stimulus to the children so there are no obstacles in the learning process. This study aimed to improve their language skills, especially in the introduction of the Arabic language mufrodat through the game of snakes and ladders in class B RA An-Nawaa I Cirebon. The subjects of this study were class B2 16 children. collection techniques are observation, interviews, and documentation. The results showed that the introduction of the language component mainly mufrodat Arabic can be introduced through the game of snakes and ladders. component of the introduction of the Arabic language can be seen before action gained 18.75% or 3 children on criteria developing with hope, in the first cycle was obtained 50% or 8 children on criteria developing very well, and criteria developing with hope 9 children, and the second cycle was obtained 81.25% or the criteria developing very well 5 children, and on developing with hope criteria 11 children.